2011
DOI: 10.2139/ssrn.1959916
|View full text |Cite
|
Sign up to set email alerts
|

Do Newspaper Articles Predict Aggregate Stock Returns?

Abstract: We analyze whether newspaper content can predict aggregate future stock returns. Our study is based on articles published in the Handelsblatt, a leading German financial newspaper, from July 1989 to March 2011. We summarize newspaper content in a systematic way by constructing word-count indices for a large number of words. Wordcount indices are instantly available and therefore potentially valuable financial indicators. Our main finding is that the predictive power of newspaper content has increased over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 39 publications
3
11
1
Order By: Relevance
“…Nonetheless, it proved useful in predicting forthcoming stock market returns in some previous studies (Ammann et al, 2014;Barber and Loeffler, 1993;Fang et al, 2014;Tetlock et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, it proved useful in predicting forthcoming stock market returns in some previous studies (Ammann et al, 2014;Barber and Loeffler, 1993;Fang et al, 2014;Tetlock et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, main reference is Ammann et al (2014) who summarized articles published in Handelsblatt, a leading financial newspaper, by constructing word count indices and found them valuable predictors of future DAX (German Stock Exchange) returns, both in and out of sample. They extended the study with cluster analysis and showed that optimal level of fragmentation of news content, for best predictive values, was seven clusters.…”
Section: Literature Review "The Stock Market Is a Device To Transfer mentioning
confidence: 99%
See 2 more Smart Citations
“…Ammann et al (2013) summarise the content of newspaper articles by means of word-count indices and use them to predict DAX 1 stock returns in and out of sample. Engelberg and Parsons (2011) show that press coverage is significantly correlated with the daily trading volume of retail investors.…”
Section: Introductionmentioning
confidence: 99%